PENDEKATAN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS X PADA MATERI ARTHROPODA - Setiani, Anggita Rizki (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This study aims to determine the results of applying differentiated learning to the learning outcomes of students on arthropod material. This research is a type of qualitative descriptive research. The subjects in this study were students in class X MIPA 5 at one of the public high schools in Banten Province. The results showed that students experienced an increase from the results of the previous assessment. In the results of the diagnostic assessment, it was found that 59% of students had completed and 41% of students had not completed. Meanwhile, on learning outcomes or formative tests, 70% of students have completed and 30% of students have not completed, so that differentiated learning greatly influences student learning outcomes.